Intellectual Property Rights, Licensing, and Innovation - Guifang Yang; Maskus, Keith E. (World Bank, Washington, DC, 2014)
There is considerable debate in economics literature on whether a decision by developing countries to strengthen their protection of intellectual property rights (IPRs) will increase or reduce their access to modern technologies invented by industrial countries. This access can be achieved through technology transfer of various kinds, including foreign direct investment and licensing. Licensing is the focus of this paper.To the extent that inventing firms choose to act more monopolistically and offer fewer technologies on the market, stronger IPRs could reduce international technology flows. However, to the extent that IPRs raise the returns to innovation and licensing, these flows would expand. In theory, the outcome depends on how IPRs affect several variables-the costs of, and returns to, international licensing; the wage advantage of workers in poor countries; the innovation process in industrial countries; and the amount of labor available for innovation and production. The authors develop a theoretical model in which firms in the North (industrial countries) innovate products of higher quality levels and decide whether to produce in the North or transfer production rights to the South (developing countries) through licensing. Different quality levels of each product are sold in equilibrium because of differences in consumers' willingness-to-pay for quality improvements. Contracting problems exist because the inventors in the North must indicate to licensees in the South whether their product is of higher or lower quality and also prevent the licensees from copying the technology. So, constraints in the model ensure that the equilibrium flow of licensing higher-quality goods meets these objectives. When the South strengthens its patent rights, copying by licensees is made costlier but the returns to licensing are increased. This change affects the dynamic decisions regarding innovation and technology transfer, which could rise or fall depending on market parameters, including the labor available for research and production. Results from the model show that the net effects depend on the balance between profits made by the Northern licensor and lower labor costs in the South. If the size of the labor force used in Northern innovation compared with that used in producing goods in both the North and South is sufficiently small (a condition that accords with reality), stronger IPRs in the South would lead to more licensing and innovation. This change would also increase the Southern wage relative to the Northern wage. So, in this model a decision by developing countries to increase their patent rights would expand global innovation and increase technology transfer. This result is consistent with recent empirical evidence. It should be noted that while the results suggest that international agreements to strengthen IPRs should expand global innovation and technology transfer through licensing, the model cannot be used for welfare analysis. Thus, while the developing countries enjoy more inward licensing, the cost per license could be higher, and prices could also rise, with an unclear overall effect on economic well-being.